Productivity and heterogeneous knowledge: Exploring the relationship in a sample of drug developers - Giulio Bottazzi; Tatiana Plotnikova (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper aims to investigate the effect of knowledge characteristics on the total factor productivity of firms developing drugs in the pharmaceutical industry. We decompose knowledge into knowledge associated with the technological firm portfolio and knowledge related to R&D projects, which represent drug development at the clinical testing stage. The latter is attributed to the knowledge of relevant markets where the drugs will be sold. The results show that the effect of technological coherence vs. market coherence and of accumulated knowledge on the productivity of firms differs. Productivity increases with the number of patents and decreases with the patent diversity and project portfolio coherence. When considering only the project knowledge, the diversity of the project portfolio positively affects productivity.
Keywords: D24; O32; L25; L65; 330; total factor productivity; diversity; coherence; knowledge; Pharmazeutische Industrie; Produktivität; Wissensintensives Unternehmen; Pharmazeutische Forschung; Diversifikation; Schätzung; Welt